PENGARUH LOCUS OF CONTROL PADA KINERJA ANALIS KREDIT DENGAN MOTIVASI DAN LINGKUNGAN KERJA SEBAGAI PEMODERASI - Radityastuti, Anak Agung Ayu Ratih; Astika, Ida Bagus Putra; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
Indonesian banking sector has been a concern of government and society because there have been various cases, such as the existence of fictitious credits which is carried out by employees of the bank. The aim of this study is to obtain empirical evidence about the influence of locus of control on the performance of credit analyst related to motivation and the working environment as moderation. The data collection methods in this study is using survey method by questionnaire as data collection technique. The number of samples in this research are 37 selected people who work as a credit analyst with saturated sampling technique. The analysis technique used is Absolute Difference Test. The results showed that the locus of control has positive effect on performance. Motivation is able to moderate the influence of locus of control on working performance. Nevertheless the working environment is not able to moderate the influence of locus of control on working performance.
Keywords: locus of control, motivation, work environment, performance